HUBUNGAN ANTARA HEMOGLOBIN, UREA, KREATININ DAN COMORBIDITY DENGAN FATIGUE PADA PASIEN DENGAN HEMODIALISIS DI RS PKU MUHAMMADIYAH YOGYAKARTA - Muhammad Nur Hasan; Arif Tirtana (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Fatigue is the negative effect which most complained by patients undergoing Hemodialysis (HD). However, fatigue has not been a concern and ignored by both patients and the health care provider, although according to some references it is concluded that fatigue is a predictor of patient’s survival rate with CKD. Fatigue is considered a normal HD effect and does not require specific actions to reduce it. Fatigue is influenced by physical, psychological, situational factors including biomarkers such as Urea, creatinine, Hemoglobin (HB) and Comorbidity. This study aims was to find the relationship between Covariates with fatigue. This descriptive correlational research design aims to determine the relationship of the level of fatigue with biochemical markers on clients with hemodialysis in Yogyakarta. The approach used in this study is cross sectional. The sample in this study were clients who underwent routine HD 2 and 3 times each week with 140 respondents. Spearman's Correlation and Pearson's Correlation was used to investigate the relationship of these variables. It was concluded that only comorbidity that statistically has a relationship with fatigue, the higher number of comorbidity, higher the level of fatigue.